Characterization Of Oil Palm Frond And Bamboo As Adsorbent For Methylene Blue Dye - Tajudin, Mifzal Thaqif Md (Universiti Sains Malaysia, 2022)
Dye is a liquid that providing a plenty of pollutants and causing contamination when it is infiltrated into the natural environment. However, it must be treated correctly in order to avoid any unpleasant effects. In this research, adsorption method was used to treat the dye. Oil palm frond (OPF) and bamboo based activated carbon was produced and used as an adsorbent to conduct the dye treatment which is methylene blue. This research has drawn its focus on the tests conducted to produce an activated carbon from oil palm frond and bamboo and to determine its effectiveness to treat the dye solution. The results of the laboratory test mainly focused on the determination of colour removal of the activated carbon produced with different dosage of adsorbent, scanning electron microscopy (SEM) analysis to identify the microstructure of the produced activated carbon and the effectiveness of the activated carbon in methylene blue treatment in terms colour, turbidity and adsorption capacity. The laboratory test results shown that the bamboo based activated carbon that is produced in carbonization temperature of 500°C has been identified as the sample that has the highest effectiveness on adsorption capacity. For the characteristic of adsorbent for bamboo, the surface charge and particle size of methylene blue and activated carbon bamboo pH adjustment of 5 by using zetasizer was −10.1 mV and 513.7 d.nm. In addition, for the adjustment pH Value of 9 was -14.1 mV and 824.8 d.mm. Moreover, for the SEM analysis the image of the bamboo based activated carbon pore indicating the pore size with ×8000 magnification size for pH value 5 at constant 0.4g dosage and 93.33 mg/L concentration methylene blue were pores of irregular sizes can be seen in the SEM image. Large number of pores are found on the surface of bamboo sample. Pore development inside the activated carbon structure is important since it will increase the adsorption capacity. Then, for the X-Ray diffraction analysis (XRD), based on the adsorbent in the pH value of 5 sample were found that the vi contain for crystalline and amorphous was 39.3% and 60.7%. The peak for the sample of adsorbent pH value of 5 were higher compare to the raw adsorbent sample and sample of adsorbent pH at 2. For the dye treatment, the highest colour removal which was 97.48% occurred when the bamboo based activated carbon dosage was 0.5g and the shaking time was 30 minutes at the pH value of 5 for the concentration of methylene blue at 93.33 mg/L. However, for the oil palm frond as adsorbent, the highest colour removal which was 93.10% occurred when the oil palm frond based activated carbon dosage was 1.0g and the shaking time was 30 minutes at the pH value of 5 where the concentration of methylene blue was 8.67 mg/L were used.